Mobile Phone and Child Mortality: The Case Of Developing Countries - Azza Mohamed Hegazy (International Journal of Economics and Financial Issues, 2016)
Using the Generalized Method of Moments (GMM) methodology on a panel dataset of 43 developing countries covering the period of 2000-2012, this study provides an econometric evidence that child mortality relates to mobile phone, health expenditure, gross domestic product per capita, female education, and Sanitation. The results imply that mobile phone isn't an important contributor in reducing child mortality. Additionally, higher per capita income, total public expenditure, female education, and access to Sanitation have a statistically significant favorable impact on child mortality. Furthermore, public health expenditure almost has an insignificant impact. The results of this study benefit the policymakers in designing policies aiming to reduce child mortality in developing countries.